2021
DOI: 10.2351/7.0000482
|View full text |Cite
|
Sign up to set email alerts
|

Material loss analysis in glass additive manufacturing by laser glass deposition

Abstract: The properties of glass (e.g., transparency, chemical and thermal inertness) are advantageous for optical, microfluidic, and chemical applications. Additive manufacturing allows the creation of complex geometries and novel functionalities. In contrast to metals and polymers, there are limited options for digitally creating transparent glass geometries. Glass becomes viscous when heated above its transition temperature. This allows a bubble-free forming but requires precise thermal management. Previously explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…In all the cases estimated losses are low, with no vaporization visible during printing or deposited onto the build plate. The low rate of vaporization presented in this work, in comparison to other reports (Sleiman et al, 2021) is ascribed to highly stable and controlled laser heating while using a small hotzone (250-400 µm in diameter), with the required laser power for printing fused silica glass being less than 5.5 W.…”
Section: Discussioncontrasting
confidence: 51%
“…In all the cases estimated losses are low, with no vaporization visible during printing or deposited onto the build plate. The low rate of vaporization presented in this work, in comparison to other reports (Sleiman et al, 2021) is ascribed to highly stable and controlled laser heating while using a small hotzone (250-400 µm in diameter), with the required laser power for printing fused silica glass being less than 5.5 W.…”
Section: Discussioncontrasting
confidence: 51%
“…The technique is similar to the one, demonstrated previously by Kinzel et al 20–23 The current 3D printer, however, uses four symmetrically placed beams surrounding the glass filament, which was fed perpendicular to the fused quartz plate. Before printing, the protective coating was removed from the filament using mechanical stripping pliers.…”
Section: Materials and Fabricationmentioning
confidence: 98%
“…Glass additive manufacturing is an emerging research topic showing an increase in publications in recent years. 20–28 Recent studies demonstrated MLA fabrication in fused silica using two-photon polymerization through a direct laser writing technique, 29 , 30 an approach that combined hot embossing with custom glass 3D printing, 31 stereolithography, 32 and microscale computed axial lithography. 33 These studies were realized by utilizing a new type of silica nanocomposite resin.…”
Section: Introductionmentioning
confidence: 99%